The role of digital literacy in developing language competences of university students - Yunusov, Yunusov (The Lingua Spectrum, 2024)
In the context of the digital transformation of society and the education system, digital literacy is becoming a necessary skill. Modern students increasingly interact with information and learning platforms through digital technologies, which requires not only the acquisition of technical skills, but also the ability to effectively use them to develop professional and academic competencies, including language skills.